Challenges to the Iraqi parliament’s functions in the post Saddam Hussein Regime - Albadry, Ammar Saadoon Salman (2014)
In the context of the parliamentary institution in Iraq, despite more than ten years after the end of the Saddam regime in 2003, the functional role of the new parliament in the Iraqi political system is still problematic with a set of inherited problems such as the country’s historical development, internal socio-political structural challenges, and the regional undertakings that tend to intervene and influence domestic politics. Therefore, the general aim of this study is to explain why, how and to what extent do historical, internal and external challenges play a vital role in influencing the performance of the new Iraqi parliament in the post-Saddam regime. This study used qualitative approach in undertaking the research. The Historical Institutionalism theory was a reference for the study’s framework of analysis. It employs elite interviews as one of the primary data sources. The interviewees were divided into three main groups - members of the Iraqi parliament, diplomats, and lecturers of political science. Both face-to-face and telephone interview techniques with those practitioners and academicians in the field were adopted. Parliamentary and governmental reports, statutes and laws were also sources for primary data in this study. Secondary data were mainly from academic writings such as books, journal articles, and theses. The findings of the study show that the legislative and supervisory role of the new Iraqi parliament has been heavily influenced by the inherited political culture, ethno-religious conflicts, the consequences of the U.S. invasion in 2003, political corruption, absence of effective laws regarding political parties, election rules, economic challenges in oil and gas activities, absence of opposition and neighbouring countries’ intervention in the Iraqi political process and security predicaments. The study recommends, among others, that there is an urgent need to generate a new dynamism of democratic political culture in Iraq by activating lively debates in the parliament; amending the constitution in order to have balanced power distribution among the key branches of the government; enacting new parties’ and election laws; safeguarding the economic interest of the country by having stringent oil and gas laws; activating the anti-corruption body, and national reconciliation, to ensure the sovereignty of the country